Restoring an Onkwehonwehnéha ecosystem - Jasmine Jimerson (Journal of Agriculture, Food Systems, and Community Development)
This is a reflective essay on Akwesasne Freedom School’s effort to recreate a community of Onkwehonwehnéha (language and culture of the Original People) knowledge-sharing for healthier and more sustainable ways of living in alignment with the natural world, for the betterment of our people, the environment, and our Haudenosaunee (They Make a House, or the Six Nations) languages.